Production of Amylase from the fungus Aspergillus niger FA6 Isolated from Iraqi Soil. (Journal of the College of Basic Education, 2023)
Filamentous fungi have been widely used to produce hydrolyticenzymes for many applications. Fungal enzymes amylase wereproduced using eight Aspergillus niger isolates from eight soil sample inIraq, were screened for amylase production. A. niger FA6 (isolated fromAL-Nasiriya soil) gave maximum amylase yield, The effect of varying pH, temperature, incubation period, carbon sources and_ nitrogensources of the medium for the productivity of amylase fromA.nigerFA6 was _ investigated. The maximum activity of amylase wasrecorded after 7 days of submerged fermentation at pH 5 and temperature30°C. from different nitrogen and carbon sources used peptone andsucrose respectively gave maximum amylase yield.